Water-based adhesive and preparation method thereof
By adopting solvent-free polymerization method with urea group monomers in aqueous binders and adding ionic polymers, the problems of reduced efficiency and increased internal resistance caused by volume changes in the charge and discharge process of silicon negative electrode are solved, and the problem of increased efficiency and internal resistance caused by volume changes during charging and discharge is achieved. Excellent mechanical properties and environmental protection, suitable for industrial production.
Patent Information
- Application Number
- CN202410779691.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to develop water-based adhesives with excellent mechanical properties under environmental protection requirements and industrial production scale, and cannot effectively deal with the severe volume changes in the silicon negative electrode during charging and discharging, resulting in increased internal resistance of the battery and reduced circulation performance.
Using solvent-free polymerization method containing urea group monomers, aqueous adhesives are prepared through free radical polymerization reaction, and ionic polymers are added to improve mechanical properties and conductivity, reduce internal resistance, and ensure environmental protection and safety. Under the premise, improve the environmental protection of production and use.
It has achieved the improvement of the mechanical properties and conductivity of water-based adhesives under environmental protection conditions, solved the problem of the reduction in efficiency of the negative electrode with high silicon content during circulation, reduced internal resistance, and ensured the integrity and safety of the electrode structure.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery adhesives, and in particular to a water-based adhesive and a preparation method thereof. Background Art
[0002] The research on energy storage technology, especially battery technology, has received extensive attention. At present, lithium batteries are the mainstream research direction of today's batteries. Compared with other batteries, lithium batteries have the advantages of high operating voltage, high energy density, long cycle life, and moderate cost. The requirements for lithium batteries in the industry can be summarized as "three highs and one long": high energy density (battery miniaturization), high charge and discharge power (fast charge and discharge), high safety (battery pack heat release and gas release control) and long service life (cycle life of more than 1000 cycles). To achieve this goal, silicon, as a new type of high-performance battery negative electrode material, has a theoretical energy density that is more than 10 times that of traditional carbon negative electrodes, and also has good ion transmission performance. There is currently a trend to replace traditional carbon negative electrodes. However, the silicon negative electrode will have a drastic volume change of up to 400% during charging and discharging, which will increase the internal resistance of the battery, reduce the cycle performance, and even cause heating problems that affect safety. To solve this problem, a suitable negative electrode binder will play a key role.
[0003] The mainstream adhesive material on the market is modified styrene-butadiene rubber (SBR) + carboxymethyl cellulose (CMC). Although SBR + CMC has good adhesion to the negative electrode graphite material of lithium-ion batteries, due to the low polarity of SBR, its adhesion to silicon materials and metal plates is greatly limited. At present, the research and development direction of new negative electrode adhesives is polyacrylic acid (PAA) adhesives, which improve the adhesion to silicon electrode materials and metal conductive plates by introducing a large number of polar functional groups in the polymer chain segments. At the same time, due to the diversity of polyacrylic acid monomer selection, PAA polymers can improve their own strength through reasonable design and maintain the structural stability of silicon negative electrodes during charging and discharging. Traditional PAA adhesives use a large number of high Tg monomers to improve strength, but too high Tg will cause the pole piece to become less flexible and affect processing performance. The introduction of urea-containing monomers can significantly improve the mechanical strength of the adhesive while ensuring processability, but urea-containing monomers usually need to be polymerized in solvents, which is not in line with future environmental protection trends.
[0004] CN114142034A discloses a method for synthesizing a PAA adhesive, which contains abundant carboxyl groups and has strong interaction with active materials, current collectors and conductive agents, and can achieve high adhesion. At the same time, the addition of urea-containing monomer 2-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)urea)ethyl methacrylate provides a strong and dynamic quadruple hydrogen bond, which can not only adapt to the stress generated by the large volume expansion negative electrode, but also effectively repair the electrode damage caused by the volume expansion, and achieve efficient self-repair. However, the synthesis of this scheme requires a relatively high amount of solvent to dissolve the reactants and post-processing, and the operation process is relatively complicated, which makes it difficult to meet environmental protection requirements and large-scale industrial production. CN115050922A discloses a water-based PAA adhesive, the preparation process of which is carried out in the aqueous phase throughout the process, and the final adhesive has good electrical properties, but it does not have sufficient mechanical strength, and cannot cope with the drastic volume changes during the charging and discharging of the silicon negative electrode to ensure the integrity of the electrode structure.
[0005] In view of this, there is an urgent need in the art to develop a water-based adhesive that can meet environmental protection requirements and have excellent mechanical properties to solve the problems faced in the prior art. Summary of the invention
[0006] Based on the above facts, the purpose of the present invention is to provide a water-based adhesive, which adopts a solvent-free polymerization method of urea group-containing monomers, improves the environmental protection and safety of production and use while ensuring performance, has excellent mechanical properties, and can solve the problem of excessive efficiency drop in high silicon content negative electrodes during the cycle.
[0007] The first aspect of the present invention provides a water-based adhesive, which is obtained by polymerization reaction of the following components in parts by weight:
[0008]
[0009] The functional monomer 1 includes one or more of a (meth)acrylate monomer, a vinyl monomer, 3,4-ethylenedioxythiophene, and 3,4-methylenedioxythiophene; the functional monomer 2 includes one or more of an ionic (meth)acrylic acid monomer and an ionic vinyl monomer; the functional monomer 3 includes one or more of a (meth)acrylic acid monomer containing a urea group and a vinyl monomer containing a urea group.
[0010] Carboxyl acid monomers
[0011] In the present invention, the carboxyl-containing acid monomer includes one or more of a (meth) acrylic acid monomer containing a carboxylic acid functional group and a vinyl acid monomer containing a carboxylic acid functional group; preferably, the carboxyl-containing acid monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; more preferably, the carboxyl-containing acid monomer is selected from one or a combination of acrylic acid and methacrylic acid.
[0012] Nitrogen-containing monomers
[0013] In the present invention, the nitrogen-containing monomer includes one or more of (meth)acrylamide monomers, vinylamide monomers, diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, and vinylpyridine; preferably, the nitrogen-containing monomer is selected from one or more of (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, N-isopropyl(meth)acrylamide, N-vinylpyrrolidone, and vinylpyridine.
[0014] Functional monomer 1
[0015] In the present invention, the functional monomer 1 includes one or more of (meth)acrylate monomers, vinyl monomers, 3,4-ethylenedioxythiophene, and 3,4-methylenedioxythiophene; preferably, the functional monomer 1 is selected from methyl (meth)acrylate monomers, sec-butyl (meth)acrylate monomers, ethyl (meth)acrylate monomers, n-butyl (meth)acrylate monomers, isobutyl (meth)acrylate monomers, tert-butyl (meth)acrylate monomers, isooctyl (meth)acrylate monomers, dodecyl (meth)acrylate monomers, coconut oil (meth)acrylate monomers, One or more of ester monomers, octadecyl (meth)acrylate monomers, dimethylaminoethyl (meth)acrylate monomers, diethylaminoethyl (meth)acrylate monomers, dimethylaminopropyl (meth)acrylate monomers, glycidyl (meth)acrylate monomers, polyethylene glycol monomethyl ether (meth)acrylate monomers, polypropylene glycol (meth)acrylate monomers, norbornyl (meth)acrylate monomers, ethylene monomers, vinyl chloride monomers, styrene monomers, vinyl acetate monomers, vinyl alcohol monomers, 3,4-ethylenedioxythiophene, and 3,4-methylenedioxythiophene.
[0016] Functional monomer 2
[0017] In the present invention, the functional monomer 2 includes one or more of an ionic (meth) acrylic monomer and an ionic vinyl monomer; preferably, the functional monomer 2 is selected from one or more of a styrene sulfonate monomer, (4-styrenesulfonyl) (trifluoromethanesulfonyl) imide, and vinylbenzenesulfonamide.
[0018] Functional monomer 3
[0019] In the present invention, the functional monomer 3 includes one or more of a (meth) acrylic monomer containing a urea group and a vinyl monomer containing a urea group; preferably, the functional monomer 3 is selected from MEEU series monomers, One or more of WAM series monomers, methacrylamide ethyl ethylene urea (MAEEU), and allophanate-containing vinyl monomers.
[0020] Initiator
[0021] In the present invention, the synthesis method of the water-based adhesive is free radical polymerization, and the initiator includes one or more of an inorganic thermal initiator, an organic thermal initiator, and a redox initiation system; preferably, the inorganic thermal initiator includes one or more of sodium persulfate, ammonium persulfate, and potassium persulfate, and the organic thermal initiator includes one or more of peroxyacyl peroxide, alkyl peroxide, and peroxyester, and the redox initiation system consists of an oxidant and a reductant, and the oxidant is selected from one or more of hydrogen peroxide, organic hydrogen peroxide, and persulfate, and the reductant is selected from one or more of pyrosulfate, sulfite, ascorbic acid, and organic sodium sulfite (FF6M); more preferably, the peroxyacyl peroxide is benzoyl peroxide, the alkyl peroxide is selected from one or more of tert-butyl hydroperoxide and isopropyl benzene peroxide, and the peroxyester is tert-butyl peroxy benzoate.
[0022] pH Buffers
[0023] In the present invention, the pH buffer includes but is not limited to one or more of sodium bicarbonate, sodium carbonate, potassium carbonate, and lithium carbonate.
[0024] Neutralizer
[0025] In the present invention, the effective ingredient of the neutralizer includes but is not limited to lithium hydroxide, for example, the neutralizer is a 10 wt % lithium hydroxide aqueous solution.
[0026] The second aspect of the present invention provides a method for preparing the water-based adhesive according to the first aspect of the present invention, comprising the following steps:
[0027] S1: adding a carboxyl-containing acid monomer, a nitrogen-containing monomer, a functional monomer 1, a functional monomer 2, and a functional monomer 3 to a portion of deionized water, and stirring evenly to obtain a monomer mixture;
[0028] S2: adding the initiator to part of the deionized water and mixing evenly to obtain an initiator solution;
[0029] S3: Add part of deionized water and pH buffer into a glass reactor, raise the temperature to 80°C under nitrogen protection, drop the monomer mixture and initiator solution into the reactor simultaneously, add the remaining deionized water twice at 100 minutes and 200 minutes, and the total dropping time is 4-8 hours;
[0030] S4: After the dropwise addition is completed, the temperature is kept at 0.5-3 hours, and then a neutralizing agent is added, followed by discharging at 70° C. to obtain the water-based adhesive.
[0031] The beneficial effects of the present invention are as follows:
[0032] The present invention provides a water-based adhesive that can solve the problem of excessively reduced efficiency of high-silicon-content negative electrodes during the cycle process. The water-based adhesive adopts a solvent-free polymerization method of urea-group-containing monomers, improves the environmental protection and safety of production and use while ensuring performance, and has excellent mechanical properties. At the same time, the water-based adhesive contains a certain amount of ionic polymer, which improves the conductivity and reduces the internal resistance without affecting the strength. DETAILED DESCRIPTION
[0033] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with specific examples and comparative examples. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified, and the raw materials and reagents used are products that can be purchased from conventional commercial channels unless otherwise specified.
[0034] The above technical solution is described below in conjunction with specific embodiments.
[0035] Example 1-5: Water-based adhesive 1-5
[0036] The water-based adhesives 1-5 of the present invention were prepared according to the formula in Table 1 below, and the preparation steps were as follows:
[0037] S1: adding a carboxyl-containing acid monomer, a nitrogen-containing monomer, a functional monomer 1, a functional monomer 2, and a functional monomer 3 into 70 g of deionized water, and stirring the mixture to obtain a monomer mixture;
[0038] S2: Add the initiator into 50 g of deionized water and mix well to obtain an initiator solution;
[0039] S3: Add 500 g of deionized water and pH buffer into a glass reactor, raise the temperature to 80° C. under nitrogen protection, and simultaneously drop the monomer mixture and the initiator solution into the reactor, and add 100 g of deionized water at 100 minutes and 200 minutes of dropping time, respectively, for a total of 4 hours;
[0040] S4: After the dropwise addition is completed, the temperature is kept for 1 hour, and then a neutralizing agent is added, followed by discharging at 70° C. to obtain the water-based adhesive 1-5.
[0041] Comparative Example 1: Adhesive 1 as a comparative example
[0042] Adhesive 1 as a comparative example was prepared according to the formula in Table 1 below, and the preparation steps were as follows:
[0043] S1: adding a carboxyl-containing acid monomer, a nitrogen-containing monomer, a functional monomer 1, a functional monomer 2, and a functional monomer 3 into 70 g of deionized water, and stirring the mixture to obtain a monomer mixture;
[0044] S2: Add the initiator into 50 g of deionized water and mix well to obtain an initiator solution;
[0045] S3: Add 500 g of deionized water and pH buffer into a glass reactor, raise the temperature to 80° C. under nitrogen protection, and simultaneously drop the monomer mixture and initiator solution into the reactor for a total of 4 hours;
[0046] S4: After the dropwise addition is completed, the mixture is kept warm for 1 hour, and then a neutralizing agent and 200 g of deionized water are added, followed by discharging the mixture at 70° C., thereby obtaining Adhesive 1 as a comparative example.
[0047] It should be noted that Comparative Example 1 does not adopt the synthesis method of the present invention, which is not within the protection scope of the present invention, and is therefore Comparative Example 1. This synthesis method will cause the solution to gel, resulting in synthesis failure.
[0048] Comparative Example 2: Adhesive 2 as a comparative example
[0049] Adhesive 2 as a comparative example was prepared according to the formula in Table 1 below, and the preparation steps were as follows:
[0050] S1: adding a carboxyl-containing acid monomer, a nitrogen-containing monomer, a functional monomer 1, a functional monomer 2, and a functional monomer 3 into 70 g of deionized water, and stirring the mixture to obtain a monomer mixture;
[0051] S2: Add the initiator into 50 g of deionized water and mix well to obtain an initiator solution;
[0052] S3: Add 500 g of deionized water and pH buffer into a glass reactor, raise the temperature to 80° C. under nitrogen protection, and simultaneously drop the monomer mixture and the initiator solution into the reactor, and add 100 g of deionized water at 100 minutes and 200 minutes of dropping time, respectively, for a total of 4 hours;
[0053] S4: After the dropwise addition is completed, the mixture is kept warm for 1 hour, and then a neutralizing agent and 200 g of deionized water are added, followed by discharging the mixture at 70° C., thereby obtaining Adhesive 2 as a comparative example.
[0054] It should be noted that the amount of functional monomer 3 and deionized water in Comparative Example 2 exceeds the protection scope of the present invention, so it is Comparative Example 2. Using excessive functional monomer 3 and deionized water will cause the solution to gel, resulting in synthesis failure.
[0055] Table 1 Raw material components of water-based adhesives 1-5 and adhesive 1-2 as comparative examples
[0056]
[0057]
[0058] The performance of the adhesives obtained in Examples 1-5 and Comparative Examples 1-2 was tested, wherein the test method for the solvent stability of the dry film was as follows:
[0059] The adhesive samples obtained in Examples 1-5 and Comparative Examples 1-2 were placed in an oven at 120°C and dried for 1 hour to obtain dry film samples. 0.1 g of each sample was taken and placed in a bottle. 10 ml of dimethyl carbonate solution was added. After standing for 24 hours, the solution was aspirated. The remaining mass of the sample was measured after drying at 120°C for 1 hour. A sample greater than 0.09 g was qualified.
[0060] Table 2 Performance test results of water-based adhesives 1-5 and adhesives 1-2 as comparative examples
[0061]
[0062]
[0063] From the results in Table 2, it can be seen that the aqueous adhesives obtained in Examples 1-5 have a high content of ionic monomers, good stability in the polymerization reaction process, and strong stability of the dry film solvent, which can meet the requirements of industrial production. However, Comparative Example 1 did not use the synthesis method of the present invention, which caused the solution to gel, resulting in synthesis failure. Comparative Example 2 used an excessive amount of functional monomer 3, which also caused the solution to gel, resulting in synthesis failure.
[0064] The adhesive obtained in Examples 1-5 was subjected to a pole piece performance test, and the test method was as follows:
[0065] S1: The adhesive obtained in Examples 1-5 is mixed with water and conductive carbon black, and then dispersed evenly using a high-speed disperser to obtain conductive adhesive samples 1-5;
[0066] S2: The active material and the conductive adhesive sample 1-5 are mixed, dispersed by a high-speed deaerator, and after uniform dispersion, the SBR emulsion and the carbon nanotube dispersion are added, and the high-speed deaerator is used to disperse again, and then the solid content is adjusted to 40% with deionized water to obtain the negative electrode sheet slurry 1-5; the dry matter ratio in the slurry is active material: PAA: conductive carbon black: SBR: carbon nanotube = 94.9:1.5:1.5:2:0.1;
[0067] S3: The negative electrode slurry 1-5 is coated on the polished copper foil using a 100 μm spacing wet film preparation device and dried in a vacuum oven at 105°C, and then rolled using a roller press to a surface density of 1.4-1.52 g / cm 3 , and obtain negative electrode sheet samples 1-5.
[0068] The active material described in the test is BYD DXB6, the conductive carbon black is Super P Li, the carbon nanotube dispersion is TUBALL 0.4% aqueous dispersion, and the SBR emulsion is Ruiong 451B.
[0069] Two commercially available adhesives were selected as the control group for the test. The test results are shown in Table 3:
[0070] Table 3 Conductive adhesive data for pole piece performance test
[0071] PAA Conductive Adhesive pH Viscosity 6rpm / cp Solid content / % Fineness / micron Example 1 6.5 2240 5.6 45 Example 2 6.6 7580 6 45 Example 3 6.73 2672 5.5 45 Example 4 6.7 4850 5.8 45 Example 5 6.9 3190 5.2 45 Commercially available sample 1 8.8 13080 6.5 80 Commercially available sample 2 9.28 15600 6.4 90
[0072] It can be seen that the adhesives obtained in Examples 1-5 have better performance than the control group in terms of dispersion with carbon black, lower slurry viscosity and more uniform dispersion. The stability test of the sample electrolyte was further conducted, and the specific method was as follows:
[0073] Resin swelling rate: After drying the sample solution at 120℃ for 1 hour, cut about 0.1g of sample, weigh it and soak it in 10g DMC solution. After 24 hours, take it out, dry it and weigh it, and calculate the mass change before and after soaking.
[0074] Swelling rate = (m0-m1) / m0*100%
[0075] Among them, m0 is the mass of the electrode before immersion, and m1 is the mass of the electrode after immersion and drying.
[0076] Pole piece expansion rate: Cut the pole piece into a sample of about 2*2cm in size, measure the thickness of the pole piece with a thickness gauge, and then soak it in 10g DMC solvent for 24 hours. Then take it out and wipe off the surface moisture, measure the sample thickness and calculate the percentage change of the pole piece thickness.
[0077] Expansion rate = (T1-T0) / T0*100%
[0078] Among them, T0 is the initial thickness of the electrode, and T1 is the thickness of the electrode after immersion and drying.
[0079] The flexibility test method is: wind the pole piece on a 5mm thick iron rod and then spread it out, visually inspect whether the pole piece has cracking, powdering and powder falling. The test results are shown in Table 4:
[0080] Table 4 Sample electrolyte stability test results
[0081] PAA Conductive Adhesive Resin swelling rate / % Pole expansion rate / % Flexibility Example 1 95.1 2.3 No obvious cracking Example 2 98.4 0.5 No obvious cracking Example 3 97.8 1.1 No obvious cracking Example 4 94.3 2.5 No obvious cracking Example 5 97.2 1.1 No obvious cracking Commercially available sample 1 92.1 3.3 Slight cracking Commercially available sample 2 87.9 2.9 No obvious cracking
[0082] From the results in Table 4, it can be seen that the adhesives obtained in Examples 1-5 have higher electrolyte resistance than the control group, which can effectively prevent the excessive erosion of the electrode by the electrolyte, and can also ensure a lower expansion rate of the electrode, which is of great benefit to the safety and process stability in production.
[0083] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A water-based adhesive, characterized in that: By weight, it is obtained by polymerization of the following components: The functional monomer 1 includes one or more of a (meth)acrylate monomer, a vinyl monomer, 3,4-ethylenedioxythiophene, and 3,4-methylenedioxythiophene; the functional monomer 2 includes one or more of an ionic (meth)acrylic acid monomer and an ionic vinyl monomer; the functional monomer 3 includes one or more of a (meth)acrylic acid monomer containing a urea group and a vinyl monomer containing a urea group.
2. The water-based adhesive according to claim 1, characterized in that: The carboxyl-containing acid monomer includes one or more of a (meth) acrylic acid monomer containing a carboxylic acid functional group and a vinyl acid monomer containing a carboxylic acid functional group; preferably, the carboxyl-containing acid monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; more preferably, the carboxyl-containing acid monomer is selected from one or a combination of acrylic acid and methacrylic acid.
3. The water-based adhesive according to claim 1, characterized in that: The nitrogen-containing monomer includes one or more of (meth)acrylamide monomers, vinylamide monomers, diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, and vinylpyridine; preferably, the nitrogen-containing monomer is selected from one or more of (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, N-isopropyl(meth)acrylamide, N-vinylpyrrolidone, and vinylpyridine.
4. The water-based adhesive according to claim 1, characterized in that: The functional monomer 1 includes one or more of (meth)acrylate monomers, vinyl monomers, 3,4-ethylenedioxythiophene, and 3,4-methylenedioxythiophene; preferably, the functional monomer 1 is selected from methyl (meth)acrylate monomers, sec-butyl (meth)acrylate monomers, ethyl (meth)acrylate monomers, n-butyl (meth)acrylate monomers, isobutyl (meth)acrylate monomers, tert-butyl (meth)acrylate monomers, isooctyl (meth)acrylate monomers, dodecyl (meth)acrylate monomers, and coconut oil (meth)acrylate monomers. , octadecyl (meth)acrylate monomer, dimethylaminoethyl (meth)acrylate monomer, diethylaminoethyl (meth)acrylate monomer, dimethylaminopropyl (meth)acrylate monomer, glycidyl (meth)acrylate monomer, polyethylene glycol monomethyl ether (meth)acrylate monomer, polypropylene glycol (meth)acrylate monomer, norbornyl (meth)acrylate monomer, ethylene monomer, vinyl chloride monomer, styrene monomer, vinyl acetate monomer, vinyl alcohol monomer, 3,4-ethylenedioxythiophene, 3,4-methylenedioxythiophene one or more.
5. The water-based adhesive according to claim 1, characterized in that: The functional monomer 2 includes one or more of an ionic (meth) acrylic monomer and an ionic vinyl monomer; preferably, the functional monomer 2 is selected from one or more of a styrene sulfonate monomer, (4-styrene sulfonyl) (trifluoromethanesulfonyl) imide, and vinylbenzenesulfonamide.
6. The water-based adhesive according to claim 1, characterized in that: The functional monomer 3 includes one or more of a (meth) acrylic monomer containing a urea group and a vinyl monomer containing a urea group; preferably, the functional monomer 3 is selected from MEEU series monomers, One or more of WAM series monomers, methacrylamide ethyl ethylene urea (MAEEU), and allophanate-containing vinyl monomers.
7. The water-based adhesive according to claim 1, characterized in that: The initiator includes one or more of an inorganic thermal initiator, an organic thermal initiator, and a redox initiation system; preferably, the inorganic thermal initiator includes one or more of sodium persulfate, ammonium persulfate, and potassium persulfate, the organic thermal initiator includes one or more of acyl peroxide, alkyl peroxide, and peroxyester, the redox initiation system consists of an oxidant and a reductant, the oxidant is selected from one or more of hydrogen peroxide, organic hydrogen peroxide, and persulfate, the reductant is selected from one or more of pyrosulfate, sulfite, ascorbic acid, and organic sodium sulfite (FF6M); more preferably, the acyl peroxide is benzoyl peroxide, the alkyl peroxide is selected from one or more of tert-butyl hydroperoxide and isopropyl benzene peroxide, and the peroxyester is tert-butyl peroxy benzoate.
8. The water-based adhesive according to claim 1, characterized in that: The pH buffer includes but is not limited to one or more of sodium bicarbonate, sodium carbonate, potassium carbonate, and lithium carbonate, and the effective ingredient of the neutralizer includes but is not limited to lithium hydroxide. 9 . The aqueous adhesive according to claim 8 , wherein the neutralizing agent is a 10 wt % lithium hydroxide aqueous solution.
10. A method for preparing a water-based adhesive according to any one of claims 1 to 9, characterized in that: The steps include: S1: adding a carboxyl-containing acid monomer, a nitrogen-containing monomer, a functional monomer 1, a functional monomer 2, and a functional monomer 3 to a portion of deionized water, and stirring the mixture to obtain a monomer mixture; S2: adding the initiator to part of the deionized water and mixing evenly to obtain an initiator solution; S3: Add part of deionized water and pH buffer into a glass reactor, raise the temperature to 80°C under nitrogen protection, drop the monomer mixture and initiator solution into the reactor simultaneously, add the remaining deionized water twice at 100 minutes and 200 minutes, and the total dropping time is 4-8 hours; S4: After the dropwise addition is completed, the temperature is kept at 0.5-3 hours, and then a neutralizing agent is added, followed by discharging at 70° C. to obtain the water-based adhesive.
Citation Information
Patent Citations
Water-based binder as well as preparation method and application thereof
CN115050922A
Cited By
Binder for carbon-coated aluminum foil, preparation method therefor and use thereof
WO2026184294A1
